Digital Marketing Strategies to Increase Online Business Sales through Social Media - Wirianda, Clara (PT FORMOSA CENDEKIA GLOBAL, 2025)
The development of technology and information has changed the habits of modern society, including in the use of the internet and social media. Globally, Indonesia holds the fourth-largest internet user base. Consequently, social media has emerged as a primary platform for digital activities, including digital marketing. This marketing approach leverages social media and the internet to enhance the reach and impact of product or service promotion. This study conducts a systematic literature review (SLR). The review analyzes digital marketing strategies implemented through social media. Data were collected from various sources such as journals, articles, and books. The results of this study aim to understand effective digital marketing methods in increasing sales through social media.